Eliminating Helplessness in Pre-School Children Relying on Proprietary Programme Entitled Optimistic Kindergarten (Global Journal of Human-Social Science, 2015)
Optimism is indispensable in increasing possibilities for achieving success. It is very crucial to develop optimism from the early childhood. Nice slogans and wonders about success do not constitute the basis of optimism. It seems that the way of one's thinking about experiences and "I will try to do something" attitude are the fundamentals of optimism. Undertaking work on learning optimism contributes to creating relaxed children and adults, which may be difficult nowadays. The aim of the article is to present such a method of working with children so as to enable them to develop themselves and live to the fullest while being motivated and ready to pick challenges waiting for everyone. The question is whether a child is willing to accept them and whether he or she can handle unpleasant consequences. It is vital that these consequences do not affect a child badly and hamper their further development.
Keywords: optimism; helplessness; acquired helplessness; optimistic kindergarten